PRAGMATICS OF NORMATIVE, ORGANIZATIONAL AND ACCOUNTING OF PUBLIC PROCUREMENT (INNOVATIVE ECONOMY, 2020)
Sysiuk S.V. PRAGMATICS OF NORMATIVE, ORGANIZATIONAL AND ACCOUNTING OF PUBLIC PROCUREMENTPurpose. The aim of the article is the identification of phased implementation of public procurement, substantiation and practical solution to the problem of ensuring the improvement of the documentary system of their provision.The structure of the tasks that serve as the basis for achieving the goal is to study the current system of public procurement to identify its features and problem areas, the establishment of procurement stages, the conditions of their passing and ways to improve.Methodology of research. The general scientific and special methods of research are used, in particular: analytical method in the analysis of normative legal acts concerning public procurements; methods of analysis, synthesis and synthesis – to study the main aspects of public procurement; abstract and logical method – to formulate the conclusions of the study.Findings. The analysis of normative maintenance of the procedure of public procurement is carried out. There are four stages of the public procurement process, namely: forecasting and planning; procurement and contract performance; accounting and reporting on public procurement; control, audit and analysis of completed contracts and, accordingly, analysis of each stage. Problematic issues are identified and ways of their solution are proposed at each stage of the procurement process.Originality. It is proposed to improve the quality of planning and forecasting of the procurement process to improve the form and individual elements of the procurement plan. It is proposed to carry out evaluation of procurement mechanisms at the stage of implementation of procurement procedure, as well as to identify qualitative requirements for the subject of procurement with the corresponding explanations. It is determined to consider control, audit and analysis as a key opportunity to use control and analytical tools to optimize procurement.Practical value. Obtained results of the study in the form of proposals, in particular on improving the documentary provision of procurement procedures, identifying qualitative requirements for the subject of procurement, as well as the use of control and analytical tools aimed at improving the regulatory and organizational – accounting provision of public procurement. They will have a positive impact on solving organizational problems in public procurement, which will make it possible to identify and use available reserves to increase the efficiency of using budget funds and provide the highest quality material and technical base of public sector entities.Key words: public procurement; accounting; analysis and control of public procurements.
Keywords: Key words; public procurement; accounting; analysis and control of public procurements.